Triterpenes with unusual modifications from the fruiting bodies of the medicinal fungus Irpex lacteus. (June 2019) - Tang, Yang; Zhao, Zhen-Zhu; Feng, Tao; Li, Zheng-Hui; Chen, He-Ping; Liu, Ji-Kai
Abstract: Ten previously undescribed triterpenoid congeners, namely irpeksolactins A–J, together with eighteen known ones, were isolated from the fruiting bodies of the rainforest-dwelling medicinal fungus Irpex lacteus . The structures of all the isolates were characterized by extensive spectroscopic approaches, including 1D & 2D NMR and MS spectroscopic methods. Irpeksolactin J displayed selective and weak cytotoxicity against the human lung cancer cell line A549 and the human hepatocellular carcinoma cell line SMMC-7721. Graphical abstract: Image 1 Highlights: Twenty-eight triterpenes are reported from Irpex lacteus. Irpeksolactin A is featured by a rare 19 (10. → 5) abeo -eburicane skeleton. Irpeksolactins F and G are featured by a rare 5, 8-peroxy bridge. Irpeksolactin J is featured by a rare 16, 24-epoxy group. Irpeksolactin J shows weak cytotoxicity.